Misoprostol versus oxytocin for labor induction in term and post-term pregnancy: randomized controlled trial - Aquino, Márcia Maria Auxiliadora de; Cecatti, José Guilherme (São Paulo Medical Journal, 2003)
CONTEXT: Misoprostol, a synthetic E1 methyl analog prostaglandin, is at present receiving attention as a cervical modifier and labor induction agent. However, there is still a need for better determination of its safety and effectiveness. OBJECTIVE: To compare intravaginal misoprostol versus intravenous oxytocin for cervical ripening and labor induction in pregnant women with unripe cervices. DESIGN: Randomized controlled trial. SETTING: The study was performed at the Leonor Mendes de Barros Maternity Hospital between November 1998 and December 2000. PARTICIPANTS: 210 pregnant women with intact membranes and indication for labor induction were selected. PROCEDURES: The women randomly received 25 µg of vaginal misoprostol every 4 hours, not exceeding 8 doses (105 women), or oxytocin in a continuous infusion (105 women). MAIN MEASUREMENTS: The main parameters measured were: latent period, time from induction to vaginal delivery, delivery route, occurrence of vaginal delivery with time, occurrence of uterine tonus alterations, hypoxia and neonatal morbidity. To verify the statistical significance of the differences between the groups, the chi-squared, Student t and log-rank tests were used. RESULTS: There were no significant differences between the groups concerning conditions for labor induction, age, parity, race, marital status, family income, initial Bishop Index and number of prenatal visits. The cesarean section rate, latent period and period from induction to vaginal delivery were significantly lower for the misoprostol group. With regard to uterine tonus alterations, tachysystole was significantly more common in the misoprostol group. However, there was no difference in hypoxia and neonatal morbidity between the groups. CONCLUSION: 25 µg of misoprostol used vaginally every 4 hours is safer and more efficient for cervical ripening and labor induction than oxytocin.